Fenomena Sosial Pernikahan Dini Di Desa Tlagasana Kecamatan Watukumpul Kabupaten Pemalang - Wahyu M., Dinda Rahmah; Amelia, Surya; Aisya, Luthfia Rihadatul; Aulia, Fatwa; Annisa, Fadya; Nabila, Shivaun; Subhi, Muhammad Rifa’i (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2024)
Early marriage is still considered normal in Tlagasana village, Watukumpul sub-district, early marriage has become a socio-cultural phenomenon that has a major influence on the lives of Indonesian people. In Tlagasana village, marriage has become commonplace or commonplace. Therefore, this study aims to examine the causes and impacts that occur as a result of early marriage. The factors that cause the phenomenon of early marriage are the occurrence of school dropouts making children in Tlagasana village not go to school and choose to get married, then the factors that cause early marriage are the thoughts of parents of children in Tlagasana village, then the environmental factor because in Tlagasana village there are many early marriage phenomena therefore early marriage has become commonplace in Tlagasana village. Keywords: phenomenon; early marriage; Tlagasana village